Influences of Temperature and Humidity on Perceived Air Quality with Radiant Panel Workstation. (2017) - He, Meiling; Li, Nianping; He, Yingdong; He, De; Wang, Kuan
Abstract: Compared with traditional air conditioning, radiant cooling workstation can create a more comfortable indoor environment and improve energy efficiency. Few studies focused on the perception of humidity and air freshness in radiant cooling environment. A series of experiments was carried out in an experimental room, where the subjects reported the perception of indoor humidity and air freshness. The obtained results showed that humidity exerted no significant effect on perceived air quality at comfortable temperature. When the environment deviated from comfortable range, subjects would feel stuffier as humidity increased. When air temperature was 30 ℃ and indoor humidity reached high level (80%), the votes on air freshness ranged from 1.0 to 1.5, while the average vote was 0.5 at moderate humidity level (60%). Nevertheless, air temperature showed negligible impact on perceived air quality when humidity was at moderate level.